Purtscher’s retinopathy – case report and literature review - Roskal-Wałek, Joanna; Gierada, Magdalena; Mackiewicz, Jerzy (Medical Studies/Studia Medyczne, 2017)
Purtscher’s retinopathy is a vision-threatening state that most frequently occurs in young or middle-aged males after head or chest injury. The main symptom reported by patients is sudden, painless deterioration of vision, which can affect one or both eyes. In most patients, the changes observed in the fundus of the eye resolve within several months, and visual acuity returns to the state from before the injury. The occurrence of ischaemic changes concerning the macula or optic nerve disc may cause permanent deterioration of visual acuity. We present a case of a 43-year-old male with Purtscher’s retinopathy after a traffic accident. The article discusses clinical image, aetiology, and the current state of knowledge concerning the possibilities in diagnostics and treatment of Purtscher’s retinopathy.